Kualitas Dan Preferensi Konsumen Terhadap Madu Lebah Apis Mellifera L. Dan Apis Dorsata F. - Suhesti, Eni; Roni, Yogi; Yanti, Rina Novia; Ningsih, Ambar Triatna; Hadinoto (Jurnal Penelitian Hasil Hutan, 2023)
The availability of honey for the people of Indonesia is met by harvesting in nature from Apis dorsata (A. dorsata) bees and livestock bees. One of the bees that is often bred is Apis mellifera (A. mellifera). Consumer considerations in choosing honey are largely determined by the quality and their preferences for the honey. This paper evaluates: 1) the quality of honey from A. mellifera and A. dorsata bees according to the standard of SNI 8664-2018, 2) the comparison of consumer preferences for the two types of honey. Honey samples were taken from harvesters in Sungai Rawa Village, Sungai Apit District, Siak Regency, and packaged in sealed bottles. The honey quality testing method is guided by SNI 8664-2018. The comparison of consumer preferences was carried out using the hedonic method using 50 panelists. The comparison of the quality of each type of honey in accordance to the SNI was descriptively analyzed. Consumer preferences were compared using a two-sample t-test. The results showed that only ash content and water-insoluble solids in A. mellifera honey met the requirements of SNI 8664-2018. Meanwhile, acidity, ash content, and water-insoluble solids of A. dorsata honey met the quality requirements of the standard. Consumer preference was higher for A. mellifera honey for color and viscosity, but for aroma, A.dorsata honey had a higher preference. Meanwhile, the taste variable and the overall level of consumer preference did not differ between the two types of honey.